2006
DOI: 10.1530/eje.1.02175
|View full text |Cite
|
Sign up to set email alerts
|

Serum adiponectin and leptin levels in relation to the metabolic syndrome, androgenic profile and somatotropic axis in healthy non-diabetic elderly men

Abstract: Objective: The relationships between adipocytokines, sex steroids and the GH/IGF-I axis is poorly studied and subject to controversy in healthy elderly male subjects. We investigated the association between both adiponectin and leptin, and the metabolic syndrome (MetS), lipid parameters, insulin sensitivity, sex steroids and IGF-I in healthy non-diabetic Lebanese men. Design and methods: In this cross-sectional study, a total of 153 healthy non-diabetic men aged 50 and above (mean age 59.3G7 years) had a detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
79
1
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 67 publications
15
79
1
8
Order By: Relevance
“…In humans there appear to be relationships between the concentrations of adipokines and dyslipidemia (10,29). Gannag-Yared et al investigated the association between adiponectin and leptin with the markers of cardiometabolic syndrome including lipid concentrations, insulin sensitivity and steroid concentrations in healthy non-diabetic Lebanese men.…”
Section: Discussionmentioning
confidence: 99%
“…In humans there appear to be relationships between the concentrations of adipokines and dyslipidemia (10,29). Gannag-Yared et al investigated the association between adiponectin and leptin with the markers of cardiometabolic syndrome including lipid concentrations, insulin sensitivity and steroid concentrations in healthy non-diabetic Lebanese men.…”
Section: Discussionmentioning
confidence: 99%
“…29,34,[45][46][47][48][49][50][51][52][53][54][55] Female data were compiled from 15 studies (26 groups of individuals), with study sample size ranging from 8 to 662 individuals and a mean sample size of 94. 29,45,46,48,50,[53][54][55][56][57][58][59][60][61][62] Lack of BMI-adiponectin association S-M Kuo and MM Halpern Among these studies, eight studies included subjects of both genders and the measurements from men and women were reported separately.…”
Section: Data Collectionmentioning
confidence: 99%
“…Some studies we compiled reported both plasma leptin and adiponectin measurements, thus allowing the correlation analysis between adiponectin and leptin. The regression analysis of male adiponectin to leptin was performed on data from seven groups 45,47,49,50,53,54 and Pearson's correlation was 0.53 (P40.05, not significant).…”
Section: Lack Of Bmi-adiponectin Association S-m Kuo and MM Halpernmentioning
confidence: 99%
“…Chez l'homme, au contraire, l'hypotestostéronémie est plutôt associée à une adiposité exagérée, à une diminution de la sensibilité à l'insuline et à un syndrome métabolique [50,52]. Les hommes aux environs de la cinquantaine, obèses mais avec un phénotype MHO, ont un taux de testostérone sérique relativement plus élevé que les hommes obèses avec anomalies métaboliques [53].…”
Section: Rôle Contrasté Des Hormones Sexuellesunclassified
“…Les hommes aux environs de la cinquantaine, obèses mais avec un phénotype MHO, ont un taux de testostérone sérique relativement plus élevé que les hommes obèses avec anomalies métaboliques [53]. Les variations de la leptine et de l'adiponectine sont associées à celle des stéroïdes sexuels, et il a été proposé que la sex hormone binding globulin (SHBG) puisse être modulée par l'adiponectine [52]. Cette conclusion est confortée par une série de données expérimentales chez l'animal et par la démonstration que l'AD-36 est capable de promouvoir la différentiation préadipocytaire, de réduire l'expression et la sécrétion de leptine et de stimuler la captation de glucose par les cellules adipeuses, tout en augmentant l'expression de divers enzymes jouant un rôle clé dans la lipogenèse [55,56].…”
Section: Rôle Contrasté Des Hormones Sexuellesunclassified